ON PREDICTION OF ROCK DESTRUCTION ON BASIS OF RECORDING THE PULSES OF ELECTROMAGNETIC RADIATION - Kurlenya M.V.; Vostretsov A.G.; Kulakov G.I.; Yakovitskaya G.E. (My University, 2001)
Effect of electromagnetic emission for rock destruction site has been considered. Mathematical model of process of crack accumulation has been discussed. It has been shown that solution of problem of algorithm synthesis for destruction prediction is absent. In connection with this, the algorithm has been created, which makes it possible to predict the rock destruction on basis of recording the pulses of electromagnetic radiation. The electromagnetic radiation is connected with process of crack formation. Non-steady Poisson process has been used as model of the pulse flux. Characteristics of efficiency of algorithm have been presented.
Keywords: 622.381:550